Investigating Middle-aged Health Literacy in Ardabil - Nasrin Fouladi; Sadegh Hazrati; Masoud Shabani; Nazila Nejaddadgar (Mashhad University of Medical Sciences, 2017)
Background and objective: Health Literacy is the capacity of individuals to obtain process and understand basic health information and services needed to make healthy decisions .Therefore, this study was designed to determine health literacy of Middle-aged in Ardabil. Methods: This Cross-Sectional study was conducted on 1049 adults aged 20-60 years attending referred Ardabil health centers in 2015. Data collecting tool was Iranian health literacy questionnaire. Data was analyzed by correlation tests, Chi-square, T-test and linear regression using SPSS (16). Results: Mean age participants were 39.59±14.1 years. 56.4 percent (n=65) were females. Most participants had Diploma and postgraduate Diploma. Participants had a weak level to access information (76.3%), moderate level in perceive data (59.9%), moderate level in judgment (57.8) and level moderate in use of information (75.1%). Conclusion: Overall, there was moderate health literacy in Middle-aged. It seems necessary training programs be designed according to the needs of Middle-aged with low health literacy. Paper Type: Research Article.